Analysis Related Factors with Behavior Use Method Contraception Long Term in Active KB Acceptors in the Family Planning Village Program in Sungai Penuh City - Nandini, Kiran; Basyir, Vaulline; Firdawati, Firdawati; Semiarty, Rima; Muhammad, Syamel; Ilmiawati, Ilmiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Method Contraception Long Term (MKJP) is possible contraception used for a period long time, more than two years, effectively and efficiently For objective space birth is more than three years or end pregnancy in couples age already fertile no want to add child Again. Based on the data obtained found that active KB acceptors that is not 51.7 % used MKJP and only 48.3% used MKJP. Analysis is done in a way univariate, bivariate, and multivariate. Research results obtained that amount children (p-value 0.016), access service health (p-value 0.329), knowledge (p value 0.003), attitude (p value 0.014), support family (p value 0.048), and source information (p value 0.009). Based on the results Multivariate obtained the most dominant factor related to behavior use of MKJP, namely knowledge with the highest OR value was 1.897.